Electromyographic study of the trapezius muscle in free movements of the arm - Guazzelli Filho, J. [UNESP]; Furlani, J.; De Freitas, V. (Electromyogr Clin Neurophysiol, 1991)
The trapezius muscle (superior, middle and inferior portions) was analyzed in 20 volunteers. The electromyographic tests were carried out using a four-channel TECA TE 2-7 electromyograph with surface- and single coaxial needle electrodes. In abduction, adduction and flexion-extension, the 3 portions show increasing and decreasing activity, respectively, from the beginning until the end of these movements. In hyperextension, the 3 portions show increasing activity from the beginning until the end of the movement, with greater participation of the middle portion. Significant differences were not observed in the electromyographic profile of the trapezius, using surface and needle electrodes.